Job stress as mediating factor for creating employee performance: A Literature Review - Suhari Mukti; Tri Wulida Afrianty; Arik Prasetya (Universitas Dharma Wacana, 2022)
role of job stress as a variable that mediates the effect of workload and work environment on employee performance. This study applies various theories, namely the theory of Job Demand Resources (JDR), and Conservation of Resources (COR) to explain the relationship between variables. As a literature study article, this article contributes to developing a conceptual framework on how to combine two different perspectives of Job Demand Resources (JDR), and Conservation of Resources (COR). This article is important for management and further research considering that not many previous studies have used this theoretical framework to test a similar research model. This study has limitations in obtaining research that examines workload, work environment in research with employee performance. However, this research brings out a new framework that illustrates the contribution of job stress to employee performance through workload and work environment.